1996
DOI: 10.1159/000291966
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Endothelin 1 Levels during Asphyxia in the Fetal Goat

Abstract: The changes in fetal carotid arterial plasma levels of endothelin-1, catecholamines, PO2, PCO2 and pH were measured after intermittent repetitive umbilical cord occlusion in late gestation pregnant goats (n = 9). Endothelin-1 levels increased to 3.58 ± 0.28 pg/ml immediately after the onset of fetal hypoxia, a level significantly higher than the respective values in the control period (p < 0.05). The elevation of fetal plasma endothelin-1 levels correlated inversely with carotid arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…The nding of elevated ET-1 plasma levels in these neonates could con rm a pathogenetic role of perinatal asphyxia as a potent trigger for ET-1 synthesis and secretion, as reported by Isozaki-Fukuda et al (5). It has been reported that ET-1 in the foetal circulation is involved in the regulation of the circulation in response to changes in acid-base balance related to foetal hypoxia, and there are experimental data showing that increased endothelin-1 levels may contribute to the maintenance of the foetal circulation during foetal asphyxia (6). In other neonatal diseases, such as persistent pulmonary hypertension, ET-1 levels correlate with the severity of the illness, with a progressive decrease upon clinical improvement (7) but, at present, there are no similar data in cases of neonatal asphyxia.…”
supporting
confidence: 62%
“…The nding of elevated ET-1 plasma levels in these neonates could con rm a pathogenetic role of perinatal asphyxia as a potent trigger for ET-1 synthesis and secretion, as reported by Isozaki-Fukuda et al (5). It has been reported that ET-1 in the foetal circulation is involved in the regulation of the circulation in response to changes in acid-base balance related to foetal hypoxia, and there are experimental data showing that increased endothelin-1 levels may contribute to the maintenance of the foetal circulation during foetal asphyxia (6). In other neonatal diseases, such as persistent pulmonary hypertension, ET-1 levels correlate with the severity of the illness, with a progressive decrease upon clinical improvement (7) but, at present, there are no similar data in cases of neonatal asphyxia.…”
supporting
confidence: 62%
“…As peripheral organs reperfuse during bradycardia, blood pressure starts to fall below saline control values (8,25). The partial loss of peripheral vasoconstriction and progressive hypotension is offset by an increase in stroke volume (25), and the release of humoral factors such as catecholamines, cortisol, and endothelin-1, which partially sustain vascular tone (28,31,47,56,63,68). Our data show there is no sex-dependent effect of MgSO 4 treatment on the progressive loss of the ability to sustain blood pressure during the secondary phase of the adaptation to asphyxia, and support previous observations showing no overall effect of MgSO 4 on the pattern of the fetal cardiovascular adaptation during the secondary phase.…”
Section: Discussionmentioning
confidence: 99%
“…The intense bradycardia observed in the current study, and other rapid cardiovascular responses such as the peripheral vasoconstriction observed by others (Giussani et al 1997), induced by cord occlusion is likely to be mediated via a combination of chemoreceptor and baroreceptor stimulation, as well as via a stimulation of cardiac mechanoreceptors following a decrease in venous return to the fetal heart (Siassi et al 1979; Itskovitz et al 1983). In addition, umbilical cord occlusion stimulates a number of hormone responses, including production of adenosine (Kubonoya & Power, 1997), ACTH/cortisol (Unno et al 1997; Green et al 2000), catecholamines (Lewis et al 1984) and endothelin‐1 (Takada et al 1996), which are implicated in fetal cardiovascular control.…”
Section: Discussionmentioning
confidence: 99%